Sustainable Food House Area (SFHA): Analysis of Community Knowledge and Behavior - Adri, Delvi; Irawati, Mimien Henie; Sueb, Sueb (Jurnal Pendidikan Sains, 2023)
This research aimed to assess the knowledge and behavior of the community regarding the Sustainable Reserve Food Garden (SRFG) program. The study was conducted in July 2016 in Jorong Lubuk Agam, Kenagarian Ampang Kuranji Koto Baru, Dharmasraya, West Sumatra. Utilizing a descriptive quantitative approach, data were collected using Accidental Random Sampling, involving 33 heads of families as respondents. The findings revealed that community knowledge and behavior related to the SRFG program were generally insufficient, with 44.1% and 47.27% of respondents, respectively, demonstrating a lack of understanding and practice. The study concludes that approximately one-third of the population has limited knowledge and engagement with the SRFG program, indicating a need for further initiatives to enhance community awareness and behavior toward the implementation of the SRFG concept. DOI: https://doi.org/10.17977/jps.v11i42023p147